2019
DOI: 10.1111/jocd.13048
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of atrophic acne scars using autologous platelet‐rich plasma vs combined subcision and autologous platelet‐rich plasma: A split‐face comparative study

Abstract: Acne scarring has a significant negative effect on the quality of life of young adults. 2 Unfortunately, despite the availability of a plethora of interventions for the treatment of acne scars, many patients remain unsatisfied. What complicates the problem is that different types of acne scars are usually present simultaneously within the same patient. Various therapeutic options had been described, such as surgical techniques (punch grafting, punch excision, and subcision), resurfacing techniques (dermabrasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Abeer A Hodeib (Gentile & Garcovich, 2020) 1 1 1 1 1 1 1 1 0 1 3 1 1 1 3 1 1 1 1 1 1 1 1 0 1 3 0 21 Zeinab A. Ibrahim (Hassan et al, 2020) 1 1 1 1 0 1 1 1 1 1 3 1 1 0 0 1 1 1 1 1 1 1 1 0 0 1 2 22 N Agamia (Nicoli et al, 2015) 1 1 1 1 0 1 0 1 0 1 3 1 1 1 0 1 1 1 1 1 1 1 1 1 0 3 1 20 Eman Nofal (Giordano et al, 2017) 1 1 1 1 0 1 0 1 0 1 3 1 1 1 1 1 1 1 1 1 1 1 1 0 0 3 2 21 Akmal Saad Hassan (Min et al, 2018)…”
Section: Item Number In Checklistmentioning
confidence: 99%
“…Abeer A Hodeib (Gentile & Garcovich, 2020) 1 1 1 1 1 1 1 1 0 1 3 1 1 1 3 1 1 1 1 1 1 1 1 0 1 3 0 21 Zeinab A. Ibrahim (Hassan et al, 2020) 1 1 1 1 0 1 1 1 1 1 3 1 1 0 0 1 1 1 1 1 1 1 1 0 0 1 2 22 N Agamia (Nicoli et al, 2015) 1 1 1 1 0 1 0 1 0 1 3 1 1 1 0 1 1 1 1 1 1 1 1 1 0 3 1 20 Eman Nofal (Giordano et al, 2017) 1 1 1 1 0 1 0 1 0 1 3 1 1 1 1 1 1 1 1 1 1 1 1 0 0 3 2 21 Akmal Saad Hassan (Min et al, 2018)…”
Section: Item Number In Checklistmentioning
confidence: 99%
“…Nofal and colleagues 55 performed the first study highlighting the improvement of atrophic acne scars with intradermal injection of PRP. In a split-face study for bilateral atrophic scars, Hassan and colleagues 56 observed similar improvements in 30 patients treated with 3 monthly sessions of intradermal PRP alone and with combined treatment of subcision followed by PRP injection. Results demonstrated that PRP alone showed a better response, fewer side effects, and shorter downtime compared with combined subcision and PRP.…”
Section: Injectable Biochemical Cuesmentioning
confidence: 84%
“…They suggested that the hematoma associated with subcision may affect the PRP growth factors. 18 A comparative study that used the combination of PRP and subcision versus subcision alone demonstrated higher improvement in the combined side (32.08%) compared to (8.33%) of subcision alone. The authors reported that the rolling acne scars showed a higher response (39.27%) followed by box-type scars (33.88%), this may be due to PRP and subcision act synergistically to improve the appearance of acne scars.…”
Section: Discussionmentioning
confidence: 96%
“…They reported that the improvement was higher on the PRP side compared to the combination side. They suggested that the hematoma associated with subcision may affect the PRP growth factors 18 . A comparative study that used the combination of PRP and subcision versus subcision alone demonstrated higher improvement in the combined side (32.08%) compared to (8.33%) of subcision alone.…”
Section: Discussionmentioning
confidence: 99%